Hospitalisation rates and characteristics for adult and childhood immunoglobulin A vasculitis in Western Australia. Issue 4 (7th April 2019) - Nossent, Johannes; Raymond, Warren; Keen, Helen; Inderjeeth, Charles; Preen, David B.
Abstract: Background: Immunoglobulin A vasculitis (IgAV) is a systemic small‐vessel vasculitis of unknown aetiology. Although commonest in children, onset in adulthood is not unusual. Aim: As Australian data are lacking, we investigated longitudinal hospitalisation rates and characteristics for both adult and paediatric IgAV patients in Western Australia (WA). Methods: Data were extracted from a state‐wide register for all first hospital contacts in WA between 1980 and 2015 for patients with a primary diagnosis of IgAV. Paediatric cases were defined as those <20 years and compared with adult cases for admission rates per 100 000, demographics, complications, length of stay (LOS) and readmission rates. Results: The study cohort included 476 children (median age 5 years; interquartile range (IQR) 3–7) and 144 adults (median age 50 years; IQR 36–77). Childhood admission rates declined from 3.85 to 0.31 over time ( P < 0.001) but age at admission and LOS remained unchanged. For adults, admission rates declined from 0.40 to 0.17 ( P = 0.02) while age at admission (43 vs 63 years, P = 0.01) and LOS (5 vs 9 days, P = 0.02) increased. More adults had renal (11.8 vs 1.3%, P < 0.01), intestinal (3.5 vs 0.8%, P = 0.04) and infectious (14.6% vs 5.3%, P < 0.01) complications. Readmission was more frequent in childhood cases (23.1% vs 7.6%, P < 0.05) occurring mostly within 30 days of discharge. Conclusion: Hospitalisation rates for adults with IgAV now nearly equal those in children as adult IgAV leads to more complications. The sharp decline in childhood IgAV admissions suggests that confidence to manage children with IgAV outside the hospital setting has increased.